MUROTTAL THERAPHY AND FINGER HANDHELD RELAXATION ON ADOLESCENT WITH DYSMINORRHEA - Andi Adriana Amal; Hasnah Hasnah; Nur Rezki Hadiyanti Z (Universitas Islam Negeri Alauddin Makassar, 2020)
Dysmenorrhoea is experienced by most girls which causes them to be absent from school repeatedly so that proper management of dysmenorrhea is needed. This study aims to determine the effectiveness of murottal therapy and finger handheld relaxation in adolescents with dysmenorrhea. This research method is a quantitative research with a quasi experiment with control group, the study population is young women with dysmenorrhea and the sample consists of 36 girls with dysmenorrhea divided into 18 respondents in the murottal therapy group and 18 respondents in the finger handheld relaxation group. The dysmenorrhea pain scale was measured by the Numeric Rating Scale (NRS). The results showed that there were significant differences before and after the intervention, both murottal therapy and finger handheld relaxation with p value <0.0001. There was no significant difference in the murottal therapy and finger handheld relaxation groups with p value = 0.486. From the results of the study, it was concluded that murottal therapy and finger handheld relaxation were effective against dysmenorrhea in adolescents so that these two interventions could be used to treat dysmenorrhea in young womenABSTRAKDismenorea dialami sebagian besar remaja perempuan yang menyebabkan ketidakhadiran mereka di sekolah secara berulang sehingga dibutuhkan manajemen dismenore yang tepat. Penelitian ini bertujuan untuk mengetahui bagaimana efektivitas murottal theraphy dan fing er handheld relaxation pada remaja dengan dismenore. Metode penelitian ini adalah penelitian kuantitatif dengan quasi eksperiment with control group, populasi penelitian adalah remaja putri dengan dismenore dan sampel terdiri dari 36 remaja putri dengan dismenore yang dibagi menjadi 18 responden pada kelompok murottal theraphy dan 18 responden pada kelompok finger handheld relaxation. Skala nyeri dismenore diukur dengan Numeric Rating Scale (NRS). Hasil penelitian menunjukkan terdapat perbedaan yang bermakna sebelum dan setelah diberikan intervensi baik murottal therapy maupun finger handheld relaxation dengan nilai p <0.0001. Tidak ada perbedaan signifikan pada kelompok murottal therapy dan finger handheld relaxation dengan nilai p=0,486. Dari hasil penelitian disimpulkan bahwa murottal therapy maupun finger handheld relaxation efektif terhadap dismenore pada remaja sehingga kedua intervensi ini dapat digunakan dalam mengatasi dismenore pada remaja putri